GAMBARAN PENYEBAB PERSALINAN SECARA SECTION CAESAREA PADA IBU PRIMIGRAVIDA DI RSUD DR. TENGKU MANSYUR KOTA TANJNGBALAI TAHUN 2018 - ROSTINA AFRIDA POHAN (LP2MTBM MAKARIOZ, 2020)
The goal of this research is to identificate the factors that influence the childbirth with section caesarea for primigravidas mather in Hospital Dr. Tengku Mansyur Kota Tanjungbalai. The design of this research is using descriptive design with total population are 254 peoples and to take the sample is using minimal sample technique and getting the sample of research are 40 people. The method to collect the data is using with fill the questioner. The result of this research showed that the dominant factor are midecal indication factor are 23 peoples(57,7%), mather indication factor are peoplezs(37,5%) and indication about fetus are 2 peoples(5%). Base childbirth with section caesaread result on this research for medical worker is sugest to develop the health promotion in level people with health information, giving poster and leaflet. That is giving information about many things that possible happen during the pregnant, toward childbirth after childbirth, one of them is about the factors that possible happen become the indication for mather to